2022
DOI: 10.3389/fnins.2022.878927
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Regulation of Stress Responses Along the Rostrocaudal Axis of the Insular Cortex in Rats

Abstract: The insular cortex (IC) has been described as a part of the central network implicated in the integration and processing of limbic information, being related to the behavioral and physiological responses to stressful events. Besides, a site-specific control of physiological functions has been reported along the rostrocaudal axis of the IC. However, a functional topography of the IC in the regulation of stress responses has never been reported. Therefore, this study aimed to investigate the impact of acute rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…On the other hand, activation of CRF receptors within the posterior IC could inhibit local CeA-projecting neurons, thus causing anxiolytic effects. This idea is further supported by previous results indicating a deactivation of posterior IC neurons during stressful events [ 34 ]. However, precluding this hypothesis, a recent study identified that CRF acting via the CRF 1 receptor depolarizes pyramidal neurons within the posterior IC [ 31 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…On the other hand, activation of CRF receptors within the posterior IC could inhibit local CeA-projecting neurons, thus causing anxiolytic effects. This idea is further supported by previous results indicating a deactivation of posterior IC neurons during stressful events [ 34 ]. However, precluding this hypothesis, a recent study identified that CRF acting via the CRF 1 receptor depolarizes pyramidal neurons within the posterior IC [ 31 ].…”
Section: Discussionsupporting
confidence: 88%
“…The injection needles (33 G, Small Parts, Miami Lakes, Florida, USA) used for intrabrain microinjection of the drugs were 1 mm longer than the guide cannulas previously fixed to the skull and were connected to a 2 μ L syringe (7002-KH, Hamilton Co., Reno, NV, USA) through a polyethylene tube (PE-10) (Clay Adams, Parsippany, NJ, USA). The drugs were injected in a volume of 100 nL/side [ 11 , 16 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These two major subcomponents of the insula are associated with distinct functions: The posterior insula integrates interoceptive, perceptual, and emotional processes and is functionally connected to sensory cortices, whereas the anterior insula domain mediates cognitive processing and salience and is functionally connected to the anterior cingulate cortex and temporal cortices. Damage to either region can lead to significant autonomic dysfunction and cardiac arrhythmias, with right‐hemisphere insular damage, in particular, being associated with autonomic dysfunction and cardiac arrhythmias (Tomeo et al., 2022 ). The extent of dysfunction following insular cortex lesions is evidenced by the increased rates of sudden death and consequent increased cardiac morbidity and mortality (Lin et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The insular cortex also plays an important role in the central control of cardiac functions as it acts directly on the autonomic nervous system ( 103 , 104 ), and is consistently implicated in stress-related social and anxiety disorders ( 105 , 106 ). Recent work has demonstrated a site-specific regulation of cardiovascular stress response along the rostro-caudal axis of the insular cortex ( 107 ). There is also accumulating evidence indicating that acute stress impacts on the normal organisation of resting-state functional brain networks ( 108 , 109 ), which include prefrontal and insular hubs, and which may serve to enable efficient coping ( 108 ).…”
Section: Heart-brain Interactionsmentioning
confidence: 99%